Comics as a Teaching and Learning Strategy in Primary Social Studies Lessons (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2022)
The use of comics in the educational field is notable for their ability to motivate and attract students’ attention. This study explores the impacts of comics as a teaching and learning strategy on the topic of ‘Our Communication’ in a Year 4 primary Social Studies class in Brunei Darussalam. The study addressed the questions on the effectiveness of comics in retaining knowledge and students’ perceptions about their use. Action research is the designated method for this study, and two cycles were conducted on different samples. The samples consisted of 18 students for Cycle 1 and 14 students for Cycle 2, both from the same government school. Intervention lessons were conducted, and semi-structured interviews on randomly selected participants. Students’ views on using comics in the classroom can be derived from dominant themes developed through thematic analysis. The findings indicated that students have a positive attitude toward applying comics in the lesson. This study concludes that comics are effective as teaching material in Social Studies.